2019
DOI: 10.1515/jpem-2018-0434
|View full text |Cite
|
Sign up to set email alerts
|

Wolcott-Rallison syndrome in Iran: a common cause of neonatal diabetes

Abstract: Background Wolcott-Rallison syndrome is a rare autosomal recessive disorder characterized by neonatal/early-onset non-autoimmune insulin-dependent diabetes, multiple epiphyseal dysphasia and growth retardation. It is caused by mutations in the gene encoding eukaryotic translation initiation factor 2α kinase 3 (EIF2AK3). We aimed to study the clinical characteristics and frequency of the disease in the Iranian population. Methods We recruited 42 patients who referred to the endocrine and metabolism clinic at M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
2
15
0
1
Order By: Relevance
“…It has been reported that up to 65% of patients with any type of monogenic diabetes present with DKA [25]. Similarly, in other cohorts, 50-70% of individuals with WRS presented with DKA [3,5]. 40% of individuals with WRS in the DPV registry experienced at least one episode of SH during follow-up and 20% of individuals with WRS experienced an episode of SH within the past treatment year.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…It has been reported that up to 65% of patients with any type of monogenic diabetes present with DKA [25]. Similarly, in other cohorts, 50-70% of individuals with WRS presented with DKA [3,5]. 40% of individuals with WRS in the DPV registry experienced at least one episode of SH during follow-up and 20% of individuals with WRS experienced an episode of SH within the past treatment year.…”
Section: Discussionmentioning
confidence: 82%
“…in North Africa, Middle East and South Asia, K ATP channel mutations are less common [5]. Instead, in consanguineous populations, EIF2AK3 mutations causing WRS account for up to 25% of PNDM cases [5,9,10]. Consistently, in the DPV cohort all patients for whom this information was available had a migration background, meaning that the patients themselves had immigrated (n = 2) or their parents were born outside the DPV countries (n = 8).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…EIF2AK3, which is found on chromosome 2p11.2, encodes a protein kinase Rlike endoplasmic reticulum kinase that is respon sible for βcell development 19) . 1) .…”
Section: Discussionmentioning
confidence: 99%